TINDAKAN SUKU DAYAK NGAJU TERHADAP HUTAN - Desi Natalia; Ediyanto Ediyanto (Jurnal Analisa Sosiologi, 2024)
The Ngaju Dayak tribe upholds ancestral traditions that are evident through attitudes of kinship and mutual cooperation. These traditions show customary ties that become moral rules that also regulate their relationship with the transcendent and that instruct Kaharingan people to belom Bahadat, which means good behavior or deeds, so that balance, harmony, and natural order will be maintained. The gap in this research is the need for social actions that arise to regulate balance, harmony, and the maintenance of natural order. This research used the qualitative research by producing narrative and descriptive data. Data sources came from interviews with Basir as well as books, journal articles, and party documents related to the issue of the Ngaju Dayak tribe's actions towards the forest. Four distinctive idealized forms of action are distinguished from some of these social actions, but certain actions appear to consist of a combination of these four idealized forms of action. Customary actions may reflect the beliefs of the Ngaju Dayak tribe. That is, plots contain value-based rationality and reflect a conscious choice of goals, including the goal of maintaining a balance between the Ngaju Dayak tribe and the forest in their utilization.